2016
DOI: 10.1016/j.jvs.2016.06.104
|View full text |Cite
|
Sign up to set email alerts
|

Microembolization is associated with transient cognitive decline in patients undergoing carotid interventions

Abstract: OBJECTIVE Carotid interventions are important in helping to reduce the risk of stroke for patients with high-grade carotid artery stenosis; however, incidence of subclinical cerebral microemboli can occur during these procedures. Previously, associations have been found between incidence of microemboli and postoperative decline in memory. We therefore sought to determine whether this decline persisted long-term and to assess changes in other cognitive domains. METHODS Patients were prospectively recruited un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 21 publications
0
23
0
2
Order By: Relevance
“…On the other hand, there is increasing evidence that carotid plaque-related cerebral embolisation may have a negative effect on cognitive function [ 76 ] (and intervention may be beneficial provided minimal intervention-related brain embolism [ 76 81 ]). Understanding is thus increasing today that the total burden of DW-MRI-depicted microembolisation in patients undergoing carotid revascularisation by CEA or CAS may be associated with transient cognitive decline [ 82 ]. In a proportion of patients, part of the deficit may persist months after the intervention [ 82 , 83 ].…”
Section: Diffusion-weighted Magnetic Resonance Imaging and Mesh-covermentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there is increasing evidence that carotid plaque-related cerebral embolisation may have a negative effect on cognitive function [ 76 ] (and intervention may be beneficial provided minimal intervention-related brain embolism [ 76 81 ]). Understanding is thus increasing today that the total burden of DW-MRI-depicted microembolisation in patients undergoing carotid revascularisation by CEA or CAS may be associated with transient cognitive decline [ 82 ]. In a proportion of patients, part of the deficit may persist months after the intervention [ 82 , 83 ].…”
Section: Diffusion-weighted Magnetic Resonance Imaging and Mesh-covermentioning
confidence: 99%
“…Understanding is thus increasing today that the total burden of DW-MRI-depicted microembolisation in patients undergoing carotid revascularisation by CEA or CAS may be associated with transient cognitive decline [ 82 ]. In a proportion of patients, part of the deficit may persist months after the intervention [ 82 , 83 ]. Thus, any carotid intervention, to have a positive impact on brain function, needs to be associated with minimised cerebral embolism.…”
Section: Diffusion-weighted Magnetic Resonance Imaging and Mesh-covermentioning
confidence: 99%
“…Studies showed that the state of ischaemia and hypoxia was associated with damage to the neural network between the brainstem or cerebellar regions and the anterior circulation ( 25 27 ). Low perfusion leads to a decrease in thrombus clearance; additionally, the formation of microemboli that result from lesions caused by cerebral vascular stenosis also leads to VCI ( 28 ). In animal studies, microemboli were found to decrease the number of brain-derived neurotrophic factors in the hippocampus and lead to impaired memory in mice ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Полученные в настоящей работе данные, как и немногочисленные сообщения других авторов, свидетельствуют о возможном ухудшении когнитивных функций после ангиореконструктивных вмешательств у пациентов с коморбидным СД 2-го типа. Так, больные с СД 2-го типа превалировали (с частотой 56%) среди пациентов с микроэмболизацией при ангиореконструкции [10]. В опубликованных в 2020 г. результатах исследования C. Kraemer и соавт.…”
Section: основные клинические и лабораторные показатели обследованныхunclassified
“…Ассоциированная с КАС микроэмболизация в ближайшем послеоперационном периоде является предиктором когнитивного снижения, которое может сохраняться до 6 мес после вмешательства [10,11]. Собственные результа-ты, а также данные других авторов позволяют нам предположить, что степень периоперационного повреждения мозга при наличии СД 2-го типа коррелирует с долгосрочными когнитивными изменениями [12].…”
unclassified